Lymphaticovenular anastomosis improves quality of life and limb volume in patients with secondary lymphedema after breast cancer treatment. Issue 5 (27th June 2019) - Phillips, Georgina S. A.; Gore, Sinclair; Ramsden, Alex; Furniss, Dominic
Abstract: Secondary lymphedema is a common side effect of breast cancer treatment, with significant impact on patients' physical and psychological well‐being. Conservative therapies are the gold standard treatment, however surgical options are becoming more popular. Lymphaticovenular anastomosis (LVA) is a supermicrosurgical procedure that aims to restore lymphatic flow by anastomosing damaged lymphatics to subcutaneous venules. We aimed to assess the effects of LVA on patients' limb volume and quality of life. Pre‐ and postoperative limb volumes and LYMQOL scores were collected for patients undergoing LVA for lymphedema secondary to breast cancer. Thirty‐seven patients underwent LVA. A significant reduction was seen in median excess limb volume postoperatively (13.3%‐6.6%, P < 0.005), with volumetric improvement seen in 78% of patients. Thirteen patients were able to discontinue compression garment use. Eighty‐six percent of patients reported improved quality of life postoperatively with median LYMQOL score increasing from 90 to 104 points ( P < 0.005). LVA is a minimally invasive surgical option for patients with early stage lymphedema. It can lead to significant volumetric improvements and in select patients, freedom from compression therapy. LVA can also lead to significant improvements in quality of life, in particular patients' mood and perception of their appearance.